PERSEPSI DOSEN TERHADAP LAYANAN APLIKASI E-LKD UIN AR-RANIRY DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTENCE MODEL (TAM) - Andika Prajana; Yuni Astuti (Universitas Pahlawan Tuanku Tambusai, 2019)
Information technology and telecommunications have an influence on educational activities from the elementary school level as well as the tertiary level. Higher Education is a formal institution that is expected to produce competent workforce that is ready to face the industrial revolution 4.0 along with technological advancements. Work skills, adaptability and a dynamic mindset become challenges for human resources, one of which is as a lecturer at tertiary institutions. In an effort to supervise the quality of lecturers at UIN Ar-Raniry Banda Aceh, Indonesia against the Tri Dharma of Higher Education they use an online application based on E-LKD (Electronic